ANALISIS PERBANDINGAN VOLUME MENGGUNAKAN ALAT TOTAL STATION DAN WATERPASS DALAM PROYEK JALAN PERUMAHAN CITRA CITY SENTUL - Alexander Sihombing; Agnes Sri Mulyani; Lolom Evalita Hutabarat (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
In Civil Engineering work, precisely determining the volume of excavation and embankment is critical to ensuring accurate work planning, efficient pricing, and seamless project execution. The estimated cost of the project budget is determined through volume calculations. This investigation aims to determine the volume of excavation and embankment by employing both Total Station and Waterpass, as well as AutoCAD Civil 3D software. The Citra City Sentul Housing Road was the subject of the study. The Average Cross-section is employed to determine the volume of excavation and embankment, and the results are analyzed using the standard deviation value. The volume of excavation and embankment is greater when calculated using Total Station than when calculated using Waterpass. There is a slight discrepancy in the standard deviation of the two instruments, specifically in the volume of excavation with Total Station (0.03%) and Waterpass (0.02%), as well as in the volume of embankment (0.02%) and 0.01%, respectively. Consequently, Waterpass has been demonstrated to be more precise than Total Station, despite Total Station being more expeditious in the measurement process.